A new framework to assess the impact of new IT-based technologies on the success of quality management system - Yiying Cao; Farah Qasim Ahmed Alyousuf (Journal of Big Data)
Abstract Today, the ever-increasing growth of technology and data has undeniably affected various industries. Due to the importance of the factor of comprehensive quality management (QM), big data, and information technology (IT) in the industry and the increasing attention to it, different attitudes regarding the ways and means of reaching it have been presented by these sources. As a result, the purpose of this research is to study new IT-based technologies related to the success of the QMS. The statistical population of this research is the managers and employees of the technology sectors, which is equal to 400 people. The sample size was equal to 196 people, and a simple random sampling method was used to obtain the sample size. This research is applied in terms of its nature and purpose, and in terms of the data collection method, it is a descriptive and survey type. PLS structural equation modeling and SPSS software were used for data analysis. The findings showed that the internet of things (IoT), business intelligence (BI), cloud computing, and distributed systems have a significant impact on the success of the QMS, while near-field communication and radio frequency identification have an impact on the success of the QMS through the intermediary variable of the IoT. Finally, the results revealed that the expert systems also affect the success of the QMS through the mediator variable of BI.